Family assessment : contemporary and cutting-edge strategies - Sperry, Len (Family therapy and counseling series, 2012)
"In an era that demands ever-increasing levels of accountability and documentation, Family Assessment is a vital tool for clinicians. It covers more than one hundred assessment methods, both the most widely strategies as well as those that are more specialized and issue specific. Techniques and instruments for assessments are summarized concisely in tables and discussed in depth in the chapters, often by the experts who developed the approaches they describe. Each chapter is also supplemented by recommended strategies for utilizing the assessment tools, as well as by case studies and observational method matrices. Readers will find the second edition of Family Assessment to provide the same comprehensive evaluation and thorough analysis as the first edition but with a fully updated focus that will invigorate the work of researchers, educators, and clinicians"